An integrative modelling approach for linking environmental flow management, ecosystem service provision and inter-stakeholder conflict. (May 2016) - Jorda-Capdevila, Dídac; Rodríguez-Labajos, Beatriz; Bardina, Mònica
Abstract: Fifteen water flow-dependent ecosystem services (ES) are modelled for the case of the Ter (Catalonia, Spain), a river with persisting intra- and inter-basin conflicts on water flows. The aim is to analyse ES response (and ensuing social reaction) to changes in water flow management, in a context of several tradeoffs and synergies driven by access to water use. We argue for a new modelling approach to integrate diverse values and perspectives through engaging with stakeholders' concerns and claims. This is done under different conditions, including droughts, wet years, and different options for managing flows. Our approach involves two stages, namely water allocation modelling, including scenario development, and ES provision modelling, including participatory design of service suitability curves. The method presented allows analysing spatial/temporal patterns and ES performance. The paper explains methodological innovation and its application to highlight the role of recurrent socio-environmental conflicts in water management decisions. Highlights: Stakeholders' engagement in ES assessment unveils socio-cultural factors driving conflicts. Participatory modelling provides useful insights on spatial and temporal distribution of ES. An integrated valuation linking the river conditions and associated benefits requires biophysical indicators. Two opposed environmentalist views compete to become the alternative to business as usual.